Lippia origanoides essential oil induces tocolytic effect in virgin rat uterus and inhibits writhing in a dysmenorrhea mouse model. (23rd May 2022) - Macêdo, Cícero André Ferreira; Paiva, Gabriela Olinda de; Menezes, Pedro Modesto Nascimento; Ribeiro, Tiago Feitosa; Brito, Mariana Coelho; Vilela, Deisy Azevedo Dourado; Duarte Filho, Luiz Antonio Miranda de Souza; Ribeiro, Fernanda Pires Rodrigues de Almeida; Lucchese, Angélica Maria; Lima, Julianeli Tolentino de; Silva, Fabrício Souza
Abstract: Ethnopharmacological relevance: The species Lippia origanoides Kunth, popularly known as "salva-de-marajó", is used in Brazilian traditional "quilombola" communities to treat menstrual cramps and uterine inflammation. Aim of the study: Evaluate the spasmolytic activity of Lippia origanoides essential oil (LOO) on experimental models of uterine conditions related to menstrual cramps and investigate its mechanism of action. Materials and methods: Virgin rat-isolated uterus was mounted in the organ bath apparatus to evaluate the spasmolytic effect of LOO on basal tonus and contractions induced by carbachol, KCl, or oxytocin. We used pharmacological agents to verify the relaxation mechanism of LOO. The evaluation of uterine contractility in virgin rats, after treatment with LOO for three consecutive days, was carried out by the construction of a concentration-response curve with oxytocin or carbachol. The primary dysmenorrhea animal model was replicated with an injection of estradiol cypionate in female mice for three consecutive days, followed by intraperitoneal application of oxytocin. Results: LOO relaxed the rat uterus precontracted with 10 −2 IU/mL oxytocin (logEC50 = 1.98 ± 0.07), 1 μM carbachol (logEC50 = 1.42 ± 0.07) or 60 mM KCl (logEC50 = 1.53 ± 0.05). It was also able relax uterus on spontaneous contractions (logEC50 = 0.41 ± 0.05). Preincubation with glibenclamide, propranolol, phentolamine or L-NAME in contractions induced by carbachol did not alter significantly the relaxing effect of LOO. However, in the presence of 4-aminopyridine, CsCl or tetraethylammonium there was a reduction of LOO potency, whereas the blockers methylene blue, ODQ, aminophylline and heparin potentiated the LOO relaxing effect. Preincubation with LOO in a Ca 2+ free medium at concentrations of 27 μg/mL or 81 μg/mL reduced the contraction induced by carbachol. The administration of LOO for 3 days did not alter uterus contractility. The treatment with LOO at 30 or 100 mg/kg intraperitoneally, or 100 mg/kg orally, inhibited writhing in female mice. The association of LOO at 10 mg/kg with nifedipine or mefenamic acid potentiated writhing inhibition in mice. Conclusions: The essential oil of L. origanoides has tocolytic activity in rat isolated uterus pre-contracted with KCl, oxytocin, or carbachol. This effect is possibly related to the opening of potassium channels (Kir, KV, and KCa ), cAMP increase, and diminution of intracellular Ca 2+ . This relaxant effect, probably, contributed to reduce the number of writhings in an animal model of dysmenorrhea being potentiated by nifedipine or mefenamic acid. Taken together, the results here presented indicate that this species has a pharmacological potential for the treatment of primary dysmenorrhea, supporting its use in folk medicine. Graphical abstract: Image 1 Highlights: Lippia origanoides essential oil (LOO) has spasmolytic effect in isolated rat uterus. The spasmolytic effect of LOO was dependent on the K + channels, cAMP increasing, and reduction of [Ca 2+ ]i. Lippia origanoides essential oil presented anti-dysmenorrhea activity in mice. Nifedipine and mefenamic acid potentiated the anti-dysmenorrhea activity of LOO.